The ranch table : recipes from a year of harvests, celebrations, and family dinners on a historic California ranch - Poett, Elizabeth; Freedman, Georgia (Magnolia Publications/William Morrow, an imprint of HarperCollinsPublishers, 2023)
"The Ranch Table celebrates Rancho San Julian in both its past, including beautiful archival images of Elizabeth's family's history on the land and recipes adapted from her ancestors' notebooks, and present, organizing the book around the ranch's most important work days, family traditions big and small, and annual celebrations. Each chapter will begin with a description of an event or a special day--the work of a branding, the joys of the annual family reunion, the fun of fall's cider press and back-to-school dinner, the quiet beauty of a winter evening spent at the kitchen table--and will provide recipes for the dishes that Elizabeth makes for those occasions"--